A construção de identidade(s) religiosa(s) no movimento "Nova Era" - Silva, Aerton Alexander de Carvalho (2008)
The change of paradigms in the current society has reached the most varied fields of the human being life, from which we detach the religiosity. ln this context, the movement "New Age" has found fertile land for its development in the varied possible religious experiences. This work, through the concept of "invisible Religion" of Thomas Luckmann, who presents the subjectivity as the place of the options ánd the construction of the religious experience from the biography of each individual searchs the understanding of some aspects of the construction of the religious identity(s) in this movement that is characterized by a sacred without place, a nomadic religiosity, favoring floating identity(s)